2011
DOI: 10.1152/ajpheart.01267.2010
|View full text |Cite
|
Sign up to set email alerts
|

Increases in plasmatrans-EETs and blood pressure reduction in spontaneously hypertensive rats

Abstract: Epoxyeicosatrienoic acids (EETs) are vasodilator, natriuretic, and antiinflammatory lipid mediators. Both cis- and trans-EETs are stored in phospholipids and in red blood cells (RBCs) in the circulation; the maximal velocity (V(max)) of trans-EET hydrolysis by soluble epoxide hydrolase (sEH) is threefold that of cis-EETs. Because RBCs of the spontaneously hypertensive rat (SHR) exhibit increased sEH activity, a deficiency of trans-EETs in the SHR was hypothesized to increase blood pressure (BP). This predictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 54 publications
2
57
0
Order By: Relevance
“…Although the same trends are seen in plasma and cortex, it is worth mentioning that the EETs/DHETEs ratio is much higher in kidney cortex than in plasma because DHETEs are predominantly located in plasma due to their higher polarity whereas EETs are largely located in the tissue. Inhibition of sEH has been shown to lower blood pressure in SHR [23,24]; however, t-AUCB did not lower blood pressure in diabetic SHR. Our data are consistent with the previously published data of Olearczyk et al [25], who showed that sEH inhibition had no effect on mean arterial pressure nor on blood glucose levels in hypertensive Goto-Kakizaki rats, as well as with our recent findings where knocking out of the sEH gene did not lower blood pressure or blood glucose in streptozotocin-induced diabetic mice [9].…”
Section: Discussionmentioning
confidence: 88%
“…Although the same trends are seen in plasma and cortex, it is worth mentioning that the EETs/DHETEs ratio is much higher in kidney cortex than in plasma because DHETEs are predominantly located in plasma due to their higher polarity whereas EETs are largely located in the tissue. Inhibition of sEH has been shown to lower blood pressure in SHR [23,24]; however, t-AUCB did not lower blood pressure in diabetic SHR. Our data are consistent with the previously published data of Olearczyk et al [25], who showed that sEH inhibition had no effect on mean arterial pressure nor on blood glucose levels in hypertensive Goto-Kakizaki rats, as well as with our recent findings where knocking out of the sEH gene did not lower blood pressure or blood glucose in streptozotocin-induced diabetic mice [9].…”
Section: Discussionmentioning
confidence: 88%
“…The cis-and trans-11,12-and -14,15-EETs were equally potent in stimulating GPR40. Cis-and trans-EET have been measured in the plasma and red blood cells and relax rat renal arcuate arteries equally (57,58). In contrast, the cis-14,15-EET was more potent than the trans-isomer in relaxing bovine coronary arteries (59).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, given the cardiovascular actions of EETs, the concept can be advanced that EETs and the modulation of their metabolic pathway could be therapeutically targeted for the treatment of hypertension and other cardiovascular diseases. For instance, EET agonists, as well as upregulation of CYP epoxygenase, have been administered chronically in experimental animal models of hypertension and metabolic syndrome and have been demonstrated to decrease blood pressure, attenuate hypertension-induced renal injury (18,22), and improve insulin signaling and vascular function (17,19,38).…”
Section: Perspectives and Significancementioning
confidence: 99%